DISTRIBUTION AND SURVIVAL OF MEGAPODIUS REINWARDT FOR ECOTOURISM CONTRIBUTING ON MOYO ISLAND - Muhammad Yamin; Khairuddin Khairuddin (Universitas Mataram, 2018)
Abstract: Megapodius reinwardt is one of the protected bird species in Indonesia. The protection toward megapodius reinwardt because of limited distribution, high economic value, has an important ecological role, has a unique, difficult breeding in captivity, the population is drastically shrinking and getting scarce.Based on this condition, the purpose of this research is to know population distribution mapping, active nest study, disturber population in order to support the atraction tourism and conservation of Megapodius reinwardt at Moyo island. Survey and observation are used to collect research data. The distributionofMegapodius reinwardt is spread around Moyo Island. The nest is located in the forest and it build by heap of soil with high 150 centimeters until 175 centimeters and diameters up to 825 cm. The location of Megapodius reinwardtnests are mostly in secundary forest than primary forest and savana at 25 m above sea level. The r-product moment correlation coefficient (r = 0,484) conclude that, Varanus sp, Sus barbatus, Prinodon linsang, Haliastur indus, Microhierax fringillarius, and human as predators are not significant to influence the nests and population of Megapodius reinwardtdecrease. So the existence of Megapodius reinwardtmanagement is needed according to in-situ cencervation on Moyo Island forEcotourism ContributingÃÂ Keywords:ÃÂ ÃÂ Ecotourism, distribution, Megapodius, survival.